1996
DOI: 10.3382/ps.0751243
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancement of the Nutritive Value of Peas for Broiler Chickens: An Evaluation of Micronization and Dehulling Processes

Abstract: The effects of dehulling and micronization (infrared heating) on the nutritive value of three cultivars (Impala, Radley, and Sirius) of peas (Pisum sativum) varying in coat color for broiler chickens were studied. Dehulling increased (P < or = 0.05) protein and starch contents and decreased (P < or = 0.05) fiber content of peas. Also, the concentrations of most amino acids slightly increased (P > or = 0.05). Micronization slightly changed (P > or = 0.05) the chemical composition of peas. Moisture, protein, fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0
9

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 33 publications
6
24
0
9
Order By: Relevance
“…Earlier studies have shown variable effects of SFM on performance in poultry. The satisfactory growth parameters of turkeys fed diet containing processed SFM was consistent with previous reports conducted on broiler chickens fed diets including sunflower (Igbasan and Guenter 1996;Laudadio et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies have shown variable effects of SFM on performance in poultry. The satisfactory growth parameters of turkeys fed diet containing processed SFM was consistent with previous reports conducted on broiler chickens fed diets including sunflower (Igbasan and Guenter 1996;Laudadio et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…The improvement in broiler performance is similar to that observed in previous work (Niu et al 2003). Birds fed micronized rye-based diets with enzyme addition had higher weight gain than broilers fed non-micronized rye-based diets (Teitge et al 1991), and broilers fed micronized peas grew faster and had a better feed efficiency than chicks fed non-micronized peas (Igbasan and Guenter 1996). Douglas et al (1991) reported that micronization of corn and low-and high-tannin sorghum improved the weight gain and feed efficiency of broilers.…”
Section: Discussionsupporting
confidence: 86%
“…Spielmann et al (2008) observed that pea protein has a low methionine content and a high arginine content. The addition of pea meal as a source of protein into broiler diets can improve carcass quality and may result in favorable lipid profile, without adversely affecting growth performance traits (Igbasan & Guenter, 1996;Pilarski et al, 2005;Laudadio et al, 2012). The broiler serum proteins and fractions can be affected by the application of different feedstaff (Bingol et al, 2016).…”
Section: Discussionmentioning
confidence: 99%